Transformational Leadership and Proactive Personality on Innovative Behavior among High School Teachers in Cirebon City - Dzakwan Ario Pangestu; Shabila Ayu Putri Islami; Putri Maylinda (Journal Research of Social Science, Economics, and Management, 2024)
The Education Era 4.0 demands the adaptation of human resources, especially teachers, to be able to produce students who are creative, think critically, and are communicative. However, there are still challenges in changing the work paradigm of teachers and education personnel towards innovation. Innovation is the key to facing new challenges and improving educational performance. The national education curriculum emphasizes the importance of preparing productive, creative, innovative, and effective human resources. However, data shows a low level of teacher innovation in Indonesia. This research aims to explore the influence of transformational leadership and proactive personality on the innovative work behavior of high school teachers in Cirebon City. Quantitative methods were used by collecting data through questionnaires distributed to teachers. The results show that transformational leadership and proactive personality have a significant effect on teachers' innovative work behavior, indicating that leaders who practice transformational leadership and teachers with proactive personalities tend to be more innovative in their work. These findings provide implications for organizational leaders in encouraging innovation in educational environments